A factor analytic structure of the conceptions of mathematics scale among pre-service mathematics teachers in South-West Nigeria - Awofala, Adeneye Olarewaju; Lawani, Abisola Olusola; Oraegbunam, Chidinma O. (JRAMathEdu (Journal of Research and Advances in Mathematics Education), 2020)
An exploration of factor analytic structure of the conceptions of mathematics scale among pre-service mathematics teachers in South-West Nigeria was conducted as evidence suggests paucity of research on psychometric properties of the conceptions of mathematics scale in Nigeria.This article through instrumentation research methodology reports the reliability and validity of the Conceptions of Mathematics Scale based on the responses of 228 pre-service mathematics teachers from five public universities in South-West Nigeria. The reliability assessed as internal consistency produced a Cronbach alpha of .88. A principal components exploration with varimax gyration established the validity of the scale as two-component archetypal accounting for 48.9% of the total variance. The dimensions were taken as Patchy Formations and Unified Formations of mathematics, as explicated in the original and other replicating studies. The factor solution could be compared to that recounted in the previous studies; hence the outcome showed the need to adopt the scale in the Nigerian context, as the pedagogy implemented during the teaching and learning of mathematics can influence students’ conceptions of mathematics. Thus, teaching mathematics with rules-based and algorithm-dependent teacher-centered pedagogies might result into rote memorization thereby leading to patchy formations while teaching mathematics as a meaningful subject full of applications to the real life could engender conceptual understanding leading to unified formations. The implication of this study is that students with patchy formation are connected with surface approaches to learning while those with unified formation of mathematics are connected with deep approaches to learning and engaging mathematics.